Wastewater treatment catalyst and preparation method thereof
By using a high-energy ball milling method to load transition metal elements on the support of the wastewater treatment catalyst and forming with the binder and curing agent, the problems of low catalyst loading and loss of effective ingredients are solved, and efficient and long-life catalyst performance is achieved.
Patent Information
- Application Number
- CN202411675411.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-21
AI Technical Summary
The loading of existing wastewater treatment catalysts is low, and the active ingredients are easily lost during use.
The high-energy ball milling method is used to load transition metal elements on the support to form a catalyst composite material, and the specific surface area and load firmness of the catalyst are improved by mixing with a binder and a curing agent.
It significantly improves the loading and performance of the catalyst, reduces the loss rate of active ingredients, extends the service life of the catalyst, and improves the efficiency of wastewater treatment.
Smart Images

Figure CN119657138A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wastewater treatment, and in particular to a wastewater treatment catalyst and a preparation method thereof. Background Art
[0002] Water resources are the basic natural resources to ensure human survival. The treatment and efficient utilization of wastewater (sewage) are urgent in chemical enterprises. Some difficult-to-degrade organic matter in industrial wastewater is the main pollutant that causes water quality deterioration. Therefore, how to effectively remove difficult-to-degrade organic matter in water has become a hot topic of research. At present, the treatment of difficult-to-degrade organic matter in wastewater (sewage) at home and abroad mainly adopts direct adsorption method and catalytic oxidation degradation method. Among them, the direct adsorption method mainly uses activated carbon adsorbent, and the catalytic oxidation method includes ozone oxidation, photocatalysis, microwave catalysis and other methods, but its core research is mainly on the research and development of catalysts.
[0003] In the treatment of mature wastewater (sewage) in printing and dyeing plants, petrochemicals, etc., catalyst degradation is a common method for treating organic matter. A large number of experiments have shown that catalysts loaded with metals or metal compounds such as manganese, zinc, copper, iron, titanium, cerium, etc. can effectively degrade phenols and heterocyclic aromatic hydrocarbons. Therefore, the preparation of catalysts has attracted much attention, and the demand has increased year by year. Among them, the catalyst carrier is also called the support, which is one of the components of the supported catalyst. At present, the catalyst carriers that are studied more at home and abroad include silica gel, activated alumina, glass fiber mesh (cloth), hollow ceramic balls, sea sand, layered graphite, molecular sieves, activated carbon, etc. In the research in the field of catalysts, it mainly includes the development and optimization of catalyst carriers, catalyst loading processes, and the catalytic mechanism and performance research of catalysts.
[0004] At present, the preparation methods of catalysts are still mainly physical and chemical methods. Physical methods such as vapor deposition have complex preparation processes and are difficult to mass produce. Chemical methods such as acid-base treatment make the raw materials react with specific reagents to form a specific pore structure inside or on the surface of the raw materials, and then use the impregnation-precipitation method to embed the catalytic metal elements into the pores of the carrier. This method requires multiple washings during the preparation process, resulting in a low final catalyst loading and a weak loading, which is easy to cause the loss of effective ingredients when used in subsequent waste (sewage) water treatment. Summary of the invention
[0005] The main purpose of the present invention is to provide a wastewater treatment catalyst and a preparation method thereof, so as to solve the problems in the prior art that the catalyst loading for wastewater treatment is low and the effective components are easily lost during use.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a method for preparing a wastewater treatment catalyst, comprising the following steps: step S1, mixing a saturated solution of a transition metal salt with a carrier, stirring and impregnating the mixture, filtering and drying the filter cake under an inert atmosphere to obtain a mixed raw material; step S2, ball-milling the mixed raw material under an air atmosphere to obtain a nano powder; step S3, mixing the nano powder with a binder and an optional curing agent, kneading and molding the mixture to obtain a spherical material or a columnar material; step S4, heating and activating the spherical material or the columnar material under an inert atmosphere to obtain a wastewater treatment catalyst.
[0007] Furthermore, in step S1, the transition metal salt includes a nitrate of a transition metal and / or a chloride of a transition metal, and the transition metal includes one or more of manganese, zinc, copper, iron, titanium and cerium; and / or the carrier includes one or more of alumina, hollow ceramic balls, layered graphite, molecular sieves, bamboo charcoal, and activated carbon; preferably, after stirring and impregnating, an alkaline solution is added to the slurry, the pH is adjusted to the complete precipitation of the transition metal, and then filtering is performed.
[0008] Furthermore, in step S1, the weight ratio of the transition metal salt to the carrier is (0.1-1):1; and / or the stirring and impregnation speed is 50-200 rpm, and the time is 20-28 hours; and / or the drying temperature is 100-120° C., and the time is 4-6 hours.
[0009] Furthermore, in step S2, the rotation speed of the ball mill is 100 to 500 rpm, the time is 1 to 5 hours, and the rotation direction is changed every 0.5 to 1 hour.
[0010] Further, in step S3, the binder includes one or more of phenolic resin, epoxy resin, asphalt and coal tar; and / or the curing agent includes one or more of aliphatic polyamine, acid anhydride, resin and polyamide; preferably, the aliphatic polyamine includes one or more of ethylenediamine, triethylamine, triethanolamine, diethylenetriamine and polyethylene polyamine; the acid anhydride includes maleic anhydride and / or phthalic anhydride; the resin includes one or more of amino resin, urea-formaldehyde resin and furfural resin.
[0011] Furthermore, in step S3, the weight ratio of the nano powder to the binder is 1:(0.1-0.8); and / or the weight ratio of the nano powder to the curing agent is 1:(0.05-0.2).
[0012] Furthermore, in step S4, the activation temperature of the heating activation is 700-1000° C., the activation time is 2-5 hours, and the water vapor introduction rate is 5-20 mL / min.
[0013] Furthermore, in step S4, the furnace temperature for heating activation is 580-620°C, and the heating rate is 5-15°C / min.
[0014] According to another aspect of the present invention, there is provided a wastewater treatment catalyst obtained using the above-mentioned preparation method of the present invention.
[0015] Furthermore, the specific surface area of the wastewater treatment catalyst is 800 to 1100 m 2 / g, COD removal rate of coal chemical wastewater ≥70%, loading capacity is 20-45%, and effective element loss rate after wastewater treatment is ≤1%.
[0016] The present invention proposes a new catalyst loading process. When loading transition metal effective components on a carrier, a high-energy ball milling method is introduced to prepare a catalyst composite material. The ball milling allows the transition metal elements and the carrier elements to undergo a chemical reaction under high-energy collision conditions, thereby increasing the loading amount of the catalyst effective elements and forming new chemical bonds to make the catalyst loading more secure, thereby effectively reducing the loss of effective components during use. After the nano powder and the binder are made into a spherical or columnar shape, the specific surface area of the catalyst is increased, which is beneficial to improving the performance of the catalyst. The prepared catalyst has a large loading amount, excellent performance and a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 A schematic diagram of a catalyst preparation process according to an embodiment of the present invention is shown;
[0019] Figure 2 shows an XRD pattern of the catalyst according to Example 1 of the present invention; and
[0020] Figure 3 The figure shows the valence diagram of the iron element in the catalyst according to Example 1 of the present invention. DETAILED DESCRIPTION
[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0022] As described in the background of the present invention, the prior art has the problem that the catalyst loading for wastewater treatment is low and the effective ingredients are easily lost during use. In order to solve the above problems, in a typical embodiment of the present invention, a method for preparing a wastewater treatment catalyst is provided, comprising the following steps: step S1, mixing a saturated solution of a transition metal salt with a carrier, stirring and impregnating, filtering and drying the filter cake under an inert atmosphere to obtain a mixed raw material; step S2, ball milling the mixed raw material under an air atmosphere to obtain a nano powder; step S3, mixing the nano powder with a binder and an optional curing agent, kneading and forming, and obtaining a spherical material or a columnar material; step S4, heating and activating the spherical material or the columnar material under an inert atmosphere to obtain a wastewater treatment catalyst.
[0023] Specifically, the present invention first mixes a saturated solution of a transition metal salt with a carrier, stirs and impregnates the mixture, and directly dries the filter cake in an inert atmosphere without washing after filtration to obtain a mixed raw material. Subsequently, the dried solid mixed raw material is ball-milled in an air atmosphere to obtain a nano powder. The ball milling device can be a stainless steel ball mill. Through ball milling, the transition metal element and the carrier element undergo a chemical reaction under the condition of high-energy collision, so that the metal element becomes a metal oxide under oxygen conditions or forms a new compound of different molecular sizes with aluminum, calcium, silicon, carbon and other elements in the carrier, thereby increasing the loading amount of the effective elements of the catalyst and forming a new chemical bond, so that the loading of the catalyst is more solid, and in the subsequent use process, the loss of effective components can be effectively reduced.
[0024] Then the nano powder is mixed with a binder and an optional curing agent, and kneaded to obtain a spherical material or a columnar material. The binder and the nano powder can be mixed into a mixed turbid liquid, and then a curing agent is added to form the mixture in one step. After being made into a spherical or columnar shape, the specific surface area of the catalyst is increased, the mesopores are well developed, and the loading capacity of the catalyst is increased. Finally, the dried spherical or columnar material is heated and activated in an inert atmosphere (for example, loaded into a tubular converter (external heating) for activation). In this process, the above raw materials undergo a series of cross-linking polycondensation reactions to form various types of pore structures to obtain a catalyst for wastewater treatment.
[0025] The present invention proposes a new catalyst loading process. When loading transition metal effective components on a carrier, the traditional single vapor deposition method or impregnation-precipitation method is changed, and a high-energy ball milling method is introduced to prepare a catalyst composite material. The ball milling allows the transition metal element and the carrier element to undergo a chemical reaction under the condition of high-energy collision, thereby increasing the loading amount of the catalyst effective elements and forming new chemical bonds to make the catalyst loading more secure, thereby reducing the loss of effective components during use. The nanometer powder and the binder are made into a spherical shape, the specific surface area of the catalyst is increased, the performance of the catalyst is significantly improved, and the prepared catalyst has a large loading amount, excellent performance and a long service life.
[0026] In summary, the method of the present invention increases the loading amount of metal active ingredients in the catalyst, and the nano-scale material obtained by ball milling has an increased specific surface area. During the use of wastewater treatment, the loss of active ingredients in the catalyst is low, thereby extending the service life of the catalyst. Taking the treatment of high-salt wastewater from coal chemical enterprises as an example, the COD removal rate can reach 50% or even more than 70%, the product has a low loss of active elements, and a long service life.
[0027] In a preferred embodiment, in step S1, the transition metal salt includes a nitrate of a transition metal and / or a chloride of a transition metal, and the transition metal includes one or more of manganese, zinc, copper, iron, titanium and cerium; and / or the carrier includes one or more of alumina, hollow ceramic balls, layered graphite, molecular sieves, bamboo charcoal, and activated carbon; preferably, after stirring and impregnating, an alkaline solution is added to the feed liquid, the pH is adjusted to completely precipitate the transition metal, and then filtered. Among them, bamboo charcoal and activated carbon only need carbonized materials. Selecting these materials as transition metal salts and carriers can not only improve the activity of the catalyst, but also enhance its stability, and is suitable for various industrial wastewater treatments, especially in coal chemical wastewater or wastewater with a high heavy metal content, showing a better removal effect. Adding alkali to adjust the pH until the transition metal is completely precipitated can make the metal elements more fully loaded inside the carrier, thereby further increasing the loading amount of the catalyst and the wastewater treatment effect.
[0028] To further improve the uniformity and activity of the catalyst, in a preferred embodiment, in step S1, the weight ratio of the transition metal salt to the carrier is (0.1-1):1; and / or the stirring and impregnation speed is 50-200 rpm, and the time is 20-28 h; and / or the drying temperature is 100-120° C., and the time is 4-6 h, which can reduce the production cost, make it more suitable for large-scale industrial production, and improve the economic benefits of wastewater treatment.
[0029] In a preferred embodiment, in step S2, the speed of the ball mill is 100 to 500 rpm, the time is 1 to 5 hours, and the rotation direction is changed every 0.5 to 1 hour. Different speeds and durations affect the loading capacity. Under the above conditions, the loading capacity of the catalyst can be further increased, the amount of catalyst used can be reduced, the cost of wastewater treatment can be reduced, and the environmental protection and economy of wastewater treatment can be improved. This ball milling process can prepare nanopowders with higher dispersion, thereby further increasing the specific surface area and activity of the catalyst to improve the efficiency and effect of wastewater treatment.
[0030] In order to further enhance the mechanical strength and corrosion resistance of the catalyst and make the effective elements less likely to fall off during use, thereby better extending the service life of the catalyst, in a preferred embodiment, in step S3, the binder includes one or more of phenolic resin, epoxy resin, asphalt and coal tar; and / or the curing agent includes one or more of aliphatic polyamines, acid anhydrides, high molecular weight resins and low molecular weight polyamides; preferably, the aliphatic polyamines include one or more of ethylenediamine, triethylamine, triethanolamine, diethylenetriamine and polyethylene polyamines; the acid anhydrides include maleic anhydride and / or phthalic anhydride; the resin includes one or more of amino resins, urea-formaldehyde resins and furfural resins.
[0031] In a preferred embodiment, in step S3, the weight ratio of the nano powder to the binder is 1:(0.1-0.8); and / or the weight ratio of the nano powder to the curing agent is 1:(0.05-0.2). By adjusting these ratios, the structure of the catalyst can be further optimized, its adsorption capacity and reaction activity in the wastewater treatment process can be improved, and the efficiency of wastewater treatment can be improved.
[0032] In order to further improve the activity and stability of the catalyst and improve the environmental protection and economy of wastewater treatment, in a preferred embodiment, in step S4, the activation temperature of the heating activation is 700-1000°C, the activation time is 2-5h, and the water vapor introduction rate is 5-20mL / min. Controlling the activation parameters within the above range can further reduce the structural damage of the catalyst during the activation process and improve the long-term stability and high efficiency of the catalyst.
[0033] Based on similar reasons, in a preferred embodiment, in step S4, the furnace entry temperature for heating activation is 580-620°C, and the heating rate is 5-15°C / min.
[0034] In another typical embodiment of the present invention, a wastewater treatment catalyst is also provided, which is obtained using the above-mentioned preparation method of the present invention. Due to the use of the preparation method of the present invention, it has significantly improved loading capacity, catalytic performance and life. The application of this catalyst in the field of wastewater treatment can not only effectively remove organic pollutants in wastewater, but also reduce the energy consumption and cost of wastewater treatment, which has important application value for improving the current status of wastewater treatment in industries such as coal chemical industry and petrochemical industry, and improving the environmental protection and economy of wastewater treatment.
[0035] In addition, this catalyst is also suitable for treating other types of industrial wastewater, such as petrochemical wastewater, electroplating wastewater, etc. It plays an important role in improving the current status of industrial wastewater treatment and promoting industrial green transformation. In practical applications, this catalyst can be integrated into wastewater treatment equipment to achieve continuous and efficient wastewater treatment, providing a new and efficient technical solution for industrial wastewater treatment, with broad application prospects and market potential.
[0036] In a preferred embodiment, the specific surface area of the wastewater treatment catalyst is 800 to 1100 m 2 / g, COD removal rate of coal chemical wastewater ≥70%, loading capacity 20-45%, and effective element loss rate after wastewater treatment ≤1%. These characteristics enable the catalyst to maintain higher efficiency and stability when treating high-concentration, difficult-to-degrade industrial wastewater, reduce the frequency of catalyst replacement, reduce the operating cost of wastewater treatment, and help improve the quality of the water environment.
[0037] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0038] Example 1
[0039] The schematic diagram of the catalyst preparation process is shown in Figure 1 .
[0040] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt, immerse it for 24 hours (stirring speed is 100rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+ After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0041] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 300 rpm for 2 hours in ambient air, with the rotation direction changed every 0.5 hours.
[0042] Step S3, mixing the phenolic resin and the ball-milled powder in a ratio of w / w=0.3:1, forming and drying.
[0043] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 2 hours, and then discharging the material to obtain a catalyst loaded with iron.
[0044] Example 2
[0045] Step S1, immerse the alumina carrier in a saturated KMnO4 salt solution in a 1:1 mass ratio with the salt, immerse for 24 hours (stirring speed is 100 rpm), filter, place in a drying oven at 110°C under nitrogen protection, and dry for 5 hours under nitrogen protection.
[0046] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 300 rpm for 3 hours in ambient air, with the rotation direction changed every 0.5 hours.
[0047] Step S3, mixing the phenolic resin and the ball-milled powder in a ratio of w / w=0.4:1, forming and drying.
[0048] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. Under a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 3 hours and then discharging the material to obtain a catalyst loaded with manganese element.
[0049] Example 3
[0050] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of Cu(NO3)2 in a mass ratio of 1:1 with salt, immerse it for 24 hours (stirring speed is 100rpm), add 1mol / L NaOH solution to adjust the pH to 6-7, so that Cu 2+ After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0051] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 400 rpm for 3 hours in ambient air, with the rotation direction changed every hour.
[0052] Step S3, coal tar and the ball-milled powder are mixed in a ratio of w / w=0.35:1, and the mixture is shaped and air-dried.
[0053] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. Under a nitrogen atmosphere, introducing water vapor at a rate of 20 mL / min, heating to 800°C, activating for 3 hours and then discharging the material to obtain a catalyst loaded with copper element.
[0054] Example 4
[0055] Step S1, immerse the hollow ceramic balls in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:0.5, immerse for 20 hours (stirring speed is 200 rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+After complete precipitation, the product was filtered and placed in a drying oven at 100°C under nitrogen protection for 6 hours.
[0056] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 300 rpm for 2 hours in ambient air, with the rotation direction changed every 0.5 hours.
[0057] Step S3, mixing the phenolic resin and the ball-milled powder in a ratio of w / w=0.3:1, forming and drying.
[0058] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 2 hours, and then discharging the material to obtain a catalyst loaded with iron.
[0059] Example 5
[0060] Step S1, immerse the bamboo charcoal in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt, immerse for 28 hours (stirring speed is 50 rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+ After complete precipitation, the product was filtered and placed in a drying oven at 120°C under nitrogen protection for 4 hours.
[0061] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 300 rpm for 2 hours in ambient air, with the rotation direction changed every 0.5 hours.
[0062] Step S3, mixing the phenolic resin and the ball-milled powder in a ratio of w / w=0.3:1, forming and drying.
[0063] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 2 hours, and then discharging the material to obtain a catalyst loaded with iron.
[0064] Example 6
[0065] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt, immerse it for 24 hours (stirring speed is 100rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+ After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0066] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 100 rpm for 5 hours in ambient air, with the rotation direction changed every hour.
[0067] Step S3, mixing the phenolic resin and the ball-milled powder in a ratio of w / w=0.3:1, forming and drying.
[0068] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 2 hours, and then discharging the material to obtain a catalyst loaded with iron.
[0069] Example 7
[0070] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt (stirring speed is 100 rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+ After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0071] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 500 rpm for 1 hour in ambient air, with the rotation direction changed every 0.5 hour.
[0072] Step S3, mixing the phenolic resin and the ball-milled powder in a ratio of w / w=0.3:1, forming and drying.
[0073] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 2 hours, and then discharging the material to obtain a catalyst loaded with iron.
[0074] Example 8
[0075] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt (stirring speed is 100 rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+ After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0076] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 300 rpm for 2 hours in ambient air, with the rotation direction changed every 0.5 hours.
[0077] Step S3, mixing the phenolic resin and the ball-milled powder in a ratio of w / w=0.1:1, forming and drying.
[0078] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 2 hours, and then discharging the material to obtain a catalyst loaded with iron.
[0079] Example 9
[0080] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt (stirring speed is 100 rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+ After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0081] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 300 rpm for 2 hours in ambient air, with the rotation direction changed every 0.5 hours.
[0082] Step S3, mixing the phenolic resin and the ball-milled powder in a ratio of w / w=0.8:1, forming and drying.
[0083] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 2 hours, and then discharging the material to obtain a catalyst loaded with iron.
[0084] Example 10
[0085] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt (stirring speed is 100 rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+ After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0086] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 300 rpm for 2 hours in ambient air, with the rotation direction changed every 0.5 hours.
[0087] Step S3, mixing the phenolic resin and the ball-milled powder in a ratio of w / w=0.3:1, forming and drying.
[0088] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 580°C and a heating rate of 5°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 5 mL / min, heating to 700°C, activating for 5 hours, and then discharging the material to obtain a catalyst loaded with iron.
[0089] Embodiment 11
[0090] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt (stirring speed is 100 rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+ After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0091] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 300 rpm for 2 hours in ambient air, with the rotation direction changed every 0.5 hours.
[0092] Step S3, mixing the phenolic resin and the ball-milled powder in a ratio of w / w=0.3:1, forming and drying.
[0093] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 620°C and a heating rate of 15°C / min. Under a nitrogen atmosphere, introducing water vapor at a rate of 20 mL / min, heating to 1000°C, activating for 2 hours and then discharging the material to obtain a catalyst loaded with iron.
[0094] Example 12
[0095] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt, immerse it for 24 hours (stirring speed is 100rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+ After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0096] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 300 rpm for 2 hours in ambient air, with the rotation direction changed every 0.5 hours.
[0097] Step S3, mixing the phenolic resin with the ball-milled powder and ethylenediamine in a ratio of w / w=0.3:1:0.05, forming and drying.
[0098] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 2 hours, and then discharging the material to obtain a catalyst loaded with iron.
[0099] Embodiment 13
[0100] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt, immerse it for 24 hours (stirring speed is 100rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+ After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0101] Step S2, placing the dried solid into a stainless steel ball mill, and running it at a speed of 300 rpm for 2 hours in ambient air, with the rotation direction changed every 0.5 hours.
[0102] Step S3, mixing the phenolic resin with the ball-milled powder and maleic anhydride in a ratio of w / w=0.3:1:0.2, forming and drying.
[0103] Step S4, placing the formed sphere into a tubular heating furnace with an entry temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 2 hours, and then discharging the material to obtain a catalyst loaded with iron.
[0104] Comparative Example 1
[0105] The difference from Example 1 is that the preparation is carried out by impregnation, precipitation and direct high temperature decomposition:
[0106] Step S1, after removing the floating dust on the surface of the Taixi anthracite-based activated carbon carbonized material, immerse it in a saturated salt solution of FeCl3·6H2O in a mass ratio of 1:1 with salt, immerse it for 24 hours (stirring speed is 100rpm), add ammonia solution (volume ratio 1:1) to adjust the pH to 4, so that Fe 3+After complete precipitation, the product was filtered and placed in a drying oven at 110°C under nitrogen protection for 5 hours.
[0107] Step S2, placing the dried solid into a tubular heating furnace at a temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 2 hours, and discharging the material to obtain a catalyst loaded with iron.
[0108] Comparative Example 2
[0109] The difference from Example 2 is that the preparation is carried out by impregnation and direct high temperature decomposition:
[0110] Step S1, immersing the alumina carrier in a saturated KMnO4 salt solution (stirring speed is 100 rpm) in a 1:1 mixed salt mass ratio, filtering, placing in a drying oven at 110° C. under nitrogen protection, and drying for 5 hours under nitrogen protection.
[0111] Step S2, placing the dried solid into a tubular heating furnace at a temperature of 600°C and a heating rate of 10°C / min. In a nitrogen atmosphere, introducing water vapor at a rate of 10 mL / min, heating to 900°C, activating for 3 hours, and discharging the material to obtain a catalyst loaded with manganese.
[0112] Comparative Example 3
[0113] Take a certain amount of activated carbon, immerse it in a 2mol / L HNO3 solution at 75℃ for 1h, wash and dry it, and then heat it to 200℃ in air and roast it for 1h to obtain the pre-treated activated carbon. Accurately weigh 4g of copper nitrate [Cu(NO3)2·3H2O], 14g of aluminum nitrate [Al(NO3)3·9H2O], and 10g of treated activated carbon, mix the three and ball mill for 8h, and roast the obtained product at 600℃ in air atmosphere for 6h, then cut it into pieces to obtain the catalyst.
[0114] The catalysts prepared in the above examples and comparative examples were tested for performance, and the results are shown in Table 1.
[0115] Test method:
[0116] Specific surface area: measured by specific surface area analyzer. Specific surface area analysis uses high-purity N2 as the probe gas, and the adsorption / desorption isotherm is measured at liquid nitrogen temperature, with a degassing temperature of 300°C and a degassing time of 6 hours. Multi-point BET models such as DFT and BJH can be used for analysis.
[0117] COD removal rate of coal chemical wastewater: After adding COD reagent to the sample to be tested, it is digested in a digester for 2 hours to fully react. Insert the COD analyzer host for measurement. The COD content of the digested sample is proportional to the absorbance value at a specific wavelength. This principle is used to determine the specific COD content in the sample.
[0118] The conversion rate of COD is calculated by the following formula:
[0119]
[0120] Where: C COD(in) is the COD concentration in the inlet solution, mg / L; C COD(out) is the COD concentration in the outlet solution, mg / L.
[0121] Loading capacity: measured by X-ray fluorescence spectrometer, XRF measurement conditions: using rhodium target X-ray tube, power 4kW, top irradiation, energy dispersive XRF instrument voltage 50kV, room temperature test. Sample preparation method using MTP-Pressed Pelle method, the activated carbon catalyst material with a grinding machine to the experimental requirements, according to the ratio of m sample: m boric acid = 2:1 added with boric acid, tablets with a tablet press, and the tablets are edged with boric acid. Mainly determined Zn, Fe, Mn, Cu and other elements.
[0122] Loss rate of effective elements after wastewater treatment: Comparison of effective element content before and after catalyst treatment of wastewater was conducted using an inductively coupled plasma emission spectrometer (ICP ion spectrometer). Before the test, the samples were treated in accordance with HJ 781-2016 "Determination of 22 Metal Elements in Solid Waste by Inductively Coupled Plasma Emission Spectrometry".
[0123] Table 1
[0124]
[0125] After testing, the specific surface area of the catalyst obtained in Example 1 is 1063m 2 / g, after ozone oxidation process treatment of coal chemical wastewater test, COD removal rate reached 85%, the loading capacity compared with the same conditions, using impregnation, precipitation, direct high temperature decomposition, compared with 10%, after treating wastewater, the effective element loss rate is 1%. The XRD diagram of the catalyst in Example 1 is shown in Figure 2 , the valence diagram of iron in the catalyst is shown in Figure 3 It can be seen that iron elements with valences of +2 and +3 appear in the catalyst, and the iron elements form new compounds with the calcium elements in the activated carbon.
[0126] After testing, the specific surface area of the catalyst obtained in Example 2 was 814m 2 / g, after ozone oxidation process treatment of coal chemical wastewater test, COD removal rate reached 70%, the loading capacity compared with the same conditions, using impregnation, direct high temperature decomposition compared with only 3% increase, because the preparation of raw materials using KMnO4 solution, without precipitation step, MnO4 - The adhesion is low, so the loading capacity is not significantly increased. The loss of effective ingredients after waste liquid treatment is 0.6%
[0127] After testing, the specific surface area of the catalyst obtained in Example 3 is 1047m 2 / g, after the ozone oxidation process was used to treat coal chemical wastewater, the COD removal rate reached 79%.
[0128] As can be seen from the above, compared with the comparative example, in each embodiment of the present invention, when loading the transition metal effective ingredient on the carrier, the high-energy ball milling method is introduced to prepare the catalyst composite material. The ball milling allows the transition metal element and the carrier element to undergo a chemical reaction under the conditions of high-energy collision, thereby increasing the loading amount of the catalyst effective element and forming new chemical bonds to make the catalyst loading more firm, thereby effectively reducing the loss of the effective ingredient during use. After the nanopowder and the binder are made into a spherical or columnar shape, the specific surface area of the catalyst is increased, which is beneficial to improving the performance of the catalyst. The prepared catalyst has a large loading amount, excellent performance and a long service life.
[0129] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the overall effect is better.
[0130] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a wastewater treatment catalyst, characterized in that: The following steps are involved: Step S1, mixing a saturated solution of a transition metal salt with a carrier, stirring and impregnating the mixture, filtering the mixture, and drying the filter cake under an inert atmosphere to obtain a mixed raw material; Step S2, ball-milling the mixed raw materials in an air atmosphere to obtain nanopowder; Step S3, mixing the nano powder with a binder and an optional curing agent, kneading and molding to obtain a spherical material or a columnar material; Step S4, heating and activating the spherical material or columnar material under an inert atmosphere to obtain the wastewater treatment catalyst.
2. The preparation method according to claim 1, characterized in that: In the step S1, The transition metal salt comprises a nitrate of a transition metal and / or a chloride of a transition metal, and the transition metal comprises one or more of manganese, zinc, copper, iron, titanium and cerium; and / or The carrier includes one or more of alumina, hollow ceramic balls, layered graphite, molecular sieves, bamboo charcoal, and activated carbon; Preferably, after the stirring and impregnation, an alkaline solution is added to the feed solution, the pH is adjusted until the transition metal is completely precipitated, and then the filtration is performed.
3. The preparation method according to claim 1 or 2, characterized in that: In the step S1, The weight ratio of the transition metal salt to the carrier is (0.1-1):1; and / or The stirring and dipping is carried out at a speed of 50 to 200 rpm for 20 to 28 hours; and / or The drying temperature is 100-120° C. and the drying time is 4-6 hours.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step S2, the rotation speed of the ball mill is 100 to 500 rpm, the time is 1 to 5 hours, and the rotation direction is changed every 0.5 to 1 hour.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S3, The binder comprises one or more of phenolic resin, epoxy resin, asphalt and coal tar; and / or The curing agent includes one or more of aliphatic polyamines, acid anhydrides, resins and polyamides; preferably, the aliphatic polyamines include one or more of ethylenediamine, triethylamine, triethanolamine, diethylenetriamine and polyethylenepolyamines; the acid anhydrides include maleic anhydride and / or phthalic anhydride; the resins include one or more of amino resins, urea-formaldehyde resins and furfural resins.
6. The preparation method according to any one of claims 1 to 5, characterized in that In the step S3, the weight ratio of the nano powder to the binder is 1:(0.1-0.8); and / or The weight ratio of the nano powder to the curing agent is 1:(0.05-0.2).
7. The preparation method according to any one of claims 1 to 6, characterized in that In the step S4, the activation temperature of the heating activation is 700-1000° C., the activation time is 2-5 hours, and the water vapor introduction rate is 5-20 mL / min.
8. The preparation method according to any one of claims 1 to 7, characterized in that In the step S4, the furnace temperature for the heating activation is 580-620°C, and the heating rate is 5-15°C / min.
9. A wastewater treatment catalyst, characterized in that The method according to any one of claims 1 to 8 is used.
10. The wastewater treatment catalyst according to claim 9, characterized in that The specific surface area of the wastewater treatment catalyst is 800 to 1100 m 2 / g, COD removal rate of coal chemical wastewater ≥70%, loading capacity is 20-45%, and effective element loss rate after wastewater treatment is ≤1%.